2019
DOI: 10.11648/j.ajmsp.20190401.16
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectral and Thermal Characterization of Cu(II) Complexes Containing Schiff Base Ligands and Their Antibacterial Activity Study

Abstract: Four complexes of Cu(II) ions containing Schiff base ligands, L 1 (C 20 H 14 O 4 N 4) [N,N`-Bis-(2-nitro-benzylidene)benzene-1,2-diamine] derived from condensation reaction of o-phenylenediamine and 2-nitrobenzaldehyde, L 2 (C 8 H 8 N 3 SCl)[2-(2-chlorobenzylidene) hydrazinecarbothioamide] derived from condensation reaction of thiosemicarbazide and ochlorobenzaldehyde and L 3 (C 9 H 11 N 3 OS) [2-(4-methoxybenzylidene)-hydrazinecarbothioamide, derived from the condensation reaction of anisaldehyde and thiosemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…For the BODIPY-PH spectrum, the characteristic peaks at 3181, 2978, 2926, 1597, and 1584 cm −1 were assigned to N-H, C methyl -H, C methyl -H, C=N, and C=N stretching vibrations, respectively. It was observed that the wavenumbers of the N-H and C=N peaks were found at the lower frequencies than those values reported in the literature [55,56], due to the larger conjugation length. After complex formation, the broad and intense O-H peak at 3231 cm −1 regarding the H 2 O ligands that coordinated to the Fe 3+ was detected.…”
Section: Sensing Properties Of Bodipy-ph Toward Ferric Ionscontrasting
confidence: 50%
“…For the BODIPY-PH spectrum, the characteristic peaks at 3181, 2978, 2926, 1597, and 1584 cm −1 were assigned to N-H, C methyl -H, C methyl -H, C=N, and C=N stretching vibrations, respectively. It was observed that the wavenumbers of the N-H and C=N peaks were found at the lower frequencies than those values reported in the literature [55,56], due to the larger conjugation length. After complex formation, the broad and intense O-H peak at 3231 cm −1 regarding the H 2 O ligands that coordinated to the Fe 3+ was detected.…”
Section: Sensing Properties Of Bodipy-ph Toward Ferric Ionscontrasting
confidence: 50%
“…The main bands assigned to N-based compounds (amine groups, both primary and secondary) are identified within the range 3460-3200 cm − 1 (stretching) [59,60]; 1610-1600 cm − 1 (bending) [19]. The presence of S-based moiety (i.e., C=S) is authenticated by the band observed at 1335-1325 cm − 1 [61]. Numerous bands attest to the presence of phosphonate groups: stretching at 1260-1250 cm − 1 (-P=O) [10], stretching at 1116-1079 cm − 1 , 940-931 cm − 1 and 546-529 cm − 1 (P-O-C) [32,62].…”
Section: Ore Treatment Applicationmentioning
confidence: 90%
“…--Additionally, the broad peak located at 1583-1519 cm − 1 (specified to aromatic C --C bonds) and adsorption band detected at 1334-1315 cm − 1 associated with the stretching vibratio of C --S bonds [68], and the broad band located at 1583-1519 cm − 1 (assigned to C --C bond, in aromatic rings) demonstrate the effective synthesis of the sorbents through the one pot reaction of thiocarbazide, trimethylphosphite, and p-phthalaldehyde. Hence, the FTIR spectra of Bis-AP and Mono-AP (Fig.…”
Section: Reminder Of Physicochemical Propertiesmentioning
confidence: 99%